LEARNING PATTERNS OF THE CHARACTER EDUCATION IN VIDYA DHARMA BUDDHIST KINDERGARTEN - Sati, Beta Widina; Dewi, Sukhitta; Kiryono, Kiryono (Jurnal Pencerahan, 2023)
This exploration aims to describe the part of the preceptors in the character education literacy and character education literacy patterns in Vidya Dharma Buddhist Kindergarten. This exploration used a descriptive qualitative approach. The subjects in this exploration were the preceptors at Vidya Dharma Buddhist Kindergarten and the scholars' parents as fresh data. The data was collected through observation, interviews and attestation styles. The exploration data was tested again using the validity of the data using triangulation. The results of this exploration showed the part of preceptors in the character education literacy, videlicet the preceptors' process in tutoring children to have a good character. Preceptors also explained and handed understanding to children about good lesson that had to be carried out, similar as tutoring children to line up before entering class, guiding children in literacy to write and coloring, training children to always supplicate before and after studying or eating, and tutoring children to always partake. to children and help each other. The character education literacy pattern in Vidya Dharma Buddhist Kindergarten was the way preceptors tutored and designed literacy. The preceptors tutored good effects, one of which is independence and good mores, similar as tutoring children to be creative by making windmills. piecemeal from that, the preceptors also tutored them to be suitable to distinguish between images. These literacy conditioning remained in agreement with the theme and relate to learning objects.